Seroprevalence of foot-and-mouth disease virus in cattle herds raised in Maasai Mara ecosystem in Kenya - Nthiwa, D.; Bett, Bernard K.; Odongo, D.; Kenya, E.; Wainaina, M.; Grazioli, S.; Foglia, E.; Brocchi, E.; Alonso, Silvia (Elsevier, 2020)
A cross-sectional study was carried out to determine foot-and-mouth disease (FMD) seroprevalence and identify risk factors of exposure among cattle herds raised in three zones with different types of land use and progressively distant from the Maasai Mara National Reserve (MMNR) boundary. We selected five villages purposively; two in zone 1 (area < 20 km from the MMNR), another two in zone 2 (area between 20-40 km away from the MMNR) and one in zone 3 (area >40 km away from the MMNR). A total of 1,170 cattle sera were collected from 390 herds in all the zones and tested for antibodies against the non-structural proteins (NSPs) of FMD virus (FMDV) using two 3ABC-based Enzyme-Linked Immunosorbent Assay (ELISA) kits. All sera samples were also screened for serotype-specific antibodies using Solid Phase Competitive ELISA (SPCE) kits (IZSLER, Italy). We targeted FMDV serotypes A, O, South African Territory [SAT] 1 and SAT 2, known to be endemic in East Africa including Kenya. Data on putative risk factors for FMD seropositivity in cattle were collected using a questionnaire. The overall apparent animal-level FMD seroprevalence based on the parallel comparison of the two anti-NSPs ELISA kits was 83.8% (95% CI; 81.8–85.9), and differed significantly across zones. Zone 1 had a higher seroprevalence than zones 2 and 3 (χ2 = 116.1, df = 2, p < 0.001). In decreasing order, the overall seroprevalences of FMDV serotypes A, SAT 2, O and SAT 1 were 26.3% (95% CI; 23.5-29.2), 21.4% (95% CI; 18.8-24.0), 21.2% (95% CI; 18.7-23.9) and 13.1% (95% CI; 11.1-15.3), respectively. The distribution of these serotypes differed significantly between zones (p < 0.05) except for SAT 2 serotype (χ2 = 0.90, df = 2, p = 0.639). Both serotypes A and O were more prevalent in zones 1 and 2 than zone 3 while serotype SAT 1, was higher in zone 3 compared to other zones. The results of multivariable analyses identified animal sex (i.e., female), raising of cattle in zones 1 and 2 (areas < 40 km away from the MMNR); mixing of cattle from multiple herds at watering points, and pastoral husbandry practices, as significant predictors of animal-level FMD seropositivity. This study established that FMD seroprevalence declined with distance from the MMNR.